1999
DOI: 10.1007/s004420050736
|View full text |Cite
|
Sign up to set email alerts
|

Insights into nitrogen and carbon dynamics of ectomycorrhizal and saprotrophic fungi from isotopic evidence

Abstract: The successful use of natural abundances of carbon (C) and nitrogen (N) isotopes in the study of ecosystem dynamics suggests that isotopic measurements could yield new insights into the role of fungi in nitrogen and carbon cycling. Sporocarps of mycorrhizal and saprotrophic fungi, vegetation, and soils were collected in young, deciduous-dominated sites and older, coniferous-dominated sites along a successional sequence at Glacier Bay National Park, Alaska. Mycorrhizal fungi had consistently higher δN and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
259
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 304 publications
(285 citation statements)
references
References 33 publications
21
259
4
Order By: Relevance
“…Fungal sheaths were 2.4 to 6.4% enriched compared to the root core. Other studies have confirmed that sporophores of ectomycorrhizal fungi are often more enriched in 15 N than sporophores of saprotrophic fungi, whereas sporophores of saprotrophic fungi are almost always enriched in 13 C compared to sporophores of ectomycorrhizal fungi (Hobbie et al, 1999;2002;Kohzu et al, 1999;2000;Taylor et al, 2003;Trudell et al, 2004). Lilleskov et al (2002) demonstrated that isotope signatures reflect ecophysiological functions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Fungal sheaths were 2.4 to 6.4% enriched compared to the root core. Other studies have confirmed that sporophores of ectomycorrhizal fungi are often more enriched in 15 N than sporophores of saprotrophic fungi, whereas sporophores of saprotrophic fungi are almost always enriched in 13 C compared to sporophores of ectomycorrhizal fungi (Hobbie et al, 1999;2002;Kohzu et al, 1999;2000;Taylor et al, 2003;Trudell et al, 2004). Lilleskov et al (2002) demonstrated that isotope signatures reflect ecophysiological functions.…”
Section: Introductionmentioning
confidence: 92%
“…They concluded that 15 N uptake was coupled with an internally fractionating process. However, Hobbie et al (1999;2001;2002), Hobbie and Colpaert (2003;, 2005) considered that in natural conditions with low nitrogen availability there is no fractionation upon uptake.…”
Section: Introductionmentioning
confidence: 99%
“…chitin, proteins or transfer amino Table 3 Per cent root-level abundance of ectomycorrhizal fungal taxa at five sites across the N deposition gradient (Lilleskov et al, 2002), their protein use status (from Table 2) and the regression of abundance of each group vs organic horizon mineral N. Sites are presented from high to low soil mineral N (from site IDs 111 to 13, respectively) acids), the proportion of fungal N uptake transferred to hosts or the allocation of N to different tissues. We know that sporocarps are isotopically enriched compared with their host plants and saprobic fungi, suggesting that fractionation during transfer of N from fungus to host is likely (Handley et al, 1996;Högberg et al, 1996Högberg et al, , 1999Hobbie et al, 1999;Kohzu et al, 2000). Variation in the specific physiology and biochemistry of N transfer, or in the proportion of N transferred to hosts, could lead to distinctive signatures among EMF.…”
Section: Nitrogen Isotopes and Protein Usementioning
confidence: 99%
“…Russula ). EMF taxa differ in their N isotopic signatures (Taylor et al , 1997;Gebauer & Taylor, 1999;Hobbie et al , 1999;Kohzu et al , 1999). Nitrogen isotopes may provide an independent line of evidence regarding N-use patterns if the combination of soil N pool signatures and physiological mechanisms of isotopic alteration during uptake, transformations, transfers and losses lead to a consistent isotopic distinction among physiological classes of fungi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation